2011
DOI: 10.1111/j.1440-169x.2011.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative modulation of bone morphogenetic protein signaling by Dullard during wing vein formation in Drosophila

Abstract: Studies in Xenopus have shown that the C-terminal domain phosphatase-like domain (CPD) phosphatase Dullard is essential for proper neural development via inhibition of bone morphogenetic protein (BMP) signaling receptors. In contrast, the orthologous budding yeast Nem1 and human Dullard have been shown to dephosphorylate the phosphatidate phosphatases yeast Smp2 ⁄ Pah1 and human Lipin, and the relationship between phospholipid metabolism and BMP signaling remain unsolved. Here we report evidence that the Dulla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…From this screen we identified Dullard, a member of the DXDX(T/V) serine/threonine phosphatase family as a potential candidate. In support of further pursuing this lead, Liu and colleagues (2011) had reported a genetic interaction between Dullard and BMP signaling in wing imaginal discs and testes23, thus we set out to build on their informative study by investigating the mechanistic basis for Dullards involvement in BMP signaling. We utilized a combination of biochemical assays and in vivo expression analyses to uncover the role this protein plays in BMP signaling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From this screen we identified Dullard, a member of the DXDX(T/V) serine/threonine phosphatase family as a potential candidate. In support of further pursuing this lead, Liu and colleagues (2011) had reported a genetic interaction between Dullard and BMP signaling in wing imaginal discs and testes23, thus we set out to build on their informative study by investigating the mechanistic basis for Dullards involvement in BMP signaling. We utilized a combination of biochemical assays and in vivo expression analyses to uncover the role this protein plays in BMP signaling.…”
Section: Resultsmentioning
confidence: 99%
“…1a,b). This semi lethal fly line was previously described23 and has a P-element inserted into the 5′UTR of the Dullard gene. Allowing these hypomorphic male larvae to mature into adults, revealed adult wings with multiple ectopic crossveins (arrows) and spurs associated with longitudinal veins 2 and 3 when compared to wild type wings (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Xenopus and Drosophila have suggested that Dullard is a negative regulator of BMP signalling 10,11 . First, we examined the messenger RNA (mRNA) expression levels of BMP2, BMP4…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that Drosophila dullard functions via lipin to regulate the production of diacylglycerol from phosphatidic acid and maintains the proper lipid composition of the nuclear membrane at nuclear pore complexes 25 . Thus, impairment of this process could affect the nuclear translocation of phosphorylated Smad proteins 11 .…”
Section: Discussionmentioning
confidence: 99%